Characterization of Ba813 harbouring Bacillus cereus in patients with haematological malignancy and hospital environments at a medical centre in Japan. Issue 7 (12th July 2020) - Aoyagi, Tetsuji; Kishihara, Yasuhiro; Ogawa, Miho; Ito, Yuki; Tanaka, Sakie; Kobayashi, Ryozo; Tokuda, Koichi; Kaku, Mistuo
Abstract : Introduction. Bacillus cereus harbouring Ba813, a specific chromosomal marker of Bacillus anthtacis, is found in patients with severe manifestations and causes nosocomial outbreaks. Aim. We assessed the genetic characteristics and virulence of Ba813 (+) B. cereus in a hospital setting. Methodology. Three neutropenic patients with haematological malignancy developed B. cereus bacteraemia within a short period. Fifteen B. cereus were isolated from different sites in a haematology ward. A total of 18 isolates were evaluated for Ba813 - and B. anthracis -related virulence, food poisoning-related virulence, genetic diversity, bacteria motility and biofilm formation. Results. Ba813 (+) B. cereus was detected in 33 % (1/3) of patients and 66 % (9/15) of the hospital environment. The 18 strains were divided into 2 major clusters (clade 1 and clade 2), and 14 strains were classified into clade 1. All Ba813 (+) strains, including four sequence types, were classified into clade 1/the cereus III lineage, which is most closely related to the anthracis lineage. Two strains belonging to clade 1/non-cereus III carried the B. anthracis -associated cap gene, but not Ba813. B. cereus, including Ba813 (+) strains, had significantly lower prevalence of enterotoxin genes than clade 2 strains. In clade 1, B. cereus, Ba813 (+) strains showed significantly higher swimming motility and biofilm formation ability than Ba813 (−) strains. Conclusion. Ba813 (+) B. cereus, which are genetically closely related to B. anthracis, were abundant in a haematological ward. Ba813 (+) B. cereus with high motility and biofilm formation abilities may spread easily in hospital environments, and could become a hospital-acquired infection.